Potential of snake fruit (Salacca zalacca) cultivars on product quality for fermented vinegar beverages - Hirankerd, W.; Tachai, S.; Darapong, P.; Sumana, B. (International Journal of Agricultural Technology, 2025)
Results showed that using naturally vinegar fermentation methods was not successful in two of the cultivars, Mo and Sumalee. Although Noen Wong did succeed in the naturally fermenting vinegar, the final product had undesirable flavor characteristics. Vinegar fermentation from all three snake fruit cultivars using the yeast, Saccharomyces cerevisiae and the Acetobacter pasteurianus bacteria, yielded the desired product of vinegar beverage. A higher level of total phenolic content was detected in the vinegars produced from Noen Wong cultivar, while those produced from Mo cultivar exhibited the highest levels of antioxidant activity. Sensory evaluation based on the 9-point hedonic scales and tested with 30 panelists, showed that vinegars produced from Mo and Sumalee cultivars showed the highest overall preference, with an average score of 6.07-6.13, which indicated a medium pleasant level of the vinegar preference. This study concluded that the Mo cultivar is found to be most suitable for making fermented vinegar beverage, however, it is recommended that the color characteristics could be improved.